Analisis Laporan Sumber Penggunaan Modal Kerja Dan Profitabilitas Perusahaan Pada Pt. Fast Food Indonesia Tbk - Margareta Desma Natalia; Ustadus Sholihin; Zulfia Rahmawati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
Reports on sources and uses of working capital can function as a basis for planning, management and supervision of working capital in the future. This research aims to determine the source and use of PT's working capital. Fast Food Indonesia Tbk and to find out the level of company profitability. This research method is a quantitative descriptive method. The data source used is secondary data. From the research results, it is known that the company's largest source of working capital comes from undetermined retained earnings, while the company's largest use of working capital is other non-current assets. The management of sources and use of the company's working capital in the 2017-2018 period was quite good, as can be seen from the increase in the current ratio and quick ratio. However, in 2019-2021 both experienced a decline. Meanwhile, the company's working capital turnover ratio is said to be effective because from 2017 to 2020 it continued to increase, but in 2021 there was a decline. Meanwhile, the company's profitability for the 2017-2021 period experienced fluctuating values. Gross Profit Margin 62.55%, 62.15%, 62.54%, 59.27%, 60.65%. Net Profit Margin 3.15%, 3.35%, 3.60%, -7.79%, -6.11%. Return On Assets 5.99%, 9.34%, 9.09%, -12.36%, -10.81%. Return On Equity 12.91%, 13.76%, 14.55%, -30.26%, -32.17%.